SELF-CONCEPTION IN THE NOVEL ”PERJALANAN TUNGGAL”: COOLEY`S LOOKING-GLASS SELF PERSPECTIVE - Aldrian, Aldrian; Chotimah, Dien Nur (Annual International Conferences on Language, Literature, and Media, 2023)
In the context of interpersonal communication, individuals have the capacity to engage in self-construction and personal transformation through internal processes. Nevertheless, an individual's self-concept is also shaped through their interactions with others. The involvement of others' views, thoughts, and responses becomes crucial for individuals in the process of discovering and conceptualizing their identity. The examination of this process of formation can be explored within the field of sociology, specifically via the lens of symbolic interaction. One of the prominent hypotheses in the field is Charles Cooley's looking-glass theory. This research uniquely employs theoretical frameworks in conducting a content analysis of the book. This research encompasses an examination of the field of literary sociology. Hence, the objective of this research endeavor is to elucidate the operational mechanisms of the looking-glass theory in the construction of self-concept as experienced by the central protagonist within the literary work entitled "Single Journey." The present study employs a qualitative methodology characterized by an analytical framework. The employed methods for data collection encompass reading and note-taking, whereas the analysis procedures encompass data reduction, data presentation, and conclusion drawing through the utilization of diverse writing instruments. The results of the analysis of the study revealed the presence of 23 data points within the object. The dataset comprises narrative context, historical self-concepts that remain undeveloped, and indicators within five self-concepts constructed by the protagonist: the dynamic idealistic self, independent self, ambitious self, loyal friend, and friendly self.